OPTIMALISASI KEBERADAAN EKOSISTEM MANGGROVE UNTUK MENCEGAH ABRASI PANTAI DI PULAU TIDUNG. - Hanca, Nambi; Putri, Dwi; Nurul, Febbry; Betris, Naomi; Mushandi, Rahmat; Setiawan, Cahyadi; Kusumawati, Lia (Jurnal Borneo Saintek, 2023)
The existence of mangroves is an ecosystem unit located in coastal areas. Coastal areas that have a lot of existence of mangrove ecosystems, of course these coastal areas will be well maintained and minimize the impact of damage that arises, as well as many marine life that is guaranteed. Mangroves have benefits as a place to live, find food, and breed marine biota. The classification of mangrove trees on Tidung Island can be differentiated based on the presence of elements present in the mangroves, namely the shape of the leaves, the shape of the stems, and the mangrove roots that stick into the coastal surface. Generally, the mangroves on Tidung Island are still around the coast. Efforts to optimize distribution in planting mangrove ecosystems are of course still being attempted in handling the preservation of coastal ecosystems around Tidung Island, both from the government and the surrounding community. The height of the mangroves on Tidung Island can be measured by how long the mangroves have been planted. The taller the mangrove trees, the greater the benefits provided to communities around the coast. In addition, mangroves can also function to prevent abrasion as well as marine biota as a place for carbon absorption (blue carbon) because basically mangroves are an important element in efforts to blue carbon in coastal areas which are useful for the continuation of human life.